DAKWAH DAN PEMBERDAYAAN MASYARAKAT - Masrial Masrial (Turast: Jurnal Penelitian dan Pengabdian, 2018)
This paper aims to describe the role of transformative da'wah in community empowerment. This is library research type by gathering various references related to da’wah. The results of the analysis shows that for the eradication of crime, that is human stupidity of all forms, in the form of kufr, polytheism, demoralization, poverty and dehumanization carried out by the method of preaching, both in the form of oral, written, and deed. Da'wah must not neglect the fulfillment of human needs as the object of da'wah consisting of material or material, spiritual or psychological dimensions, and social or social aspects.